Base-catalyzed hydrolysis of spectinomycin in aqueous solutions: Kinetics and mechanisms. (January 2023) - Song, Siqi; Jiang, Mingye; Liu, Huiling; Yao, Jie; Zhang, Xiaoyuan; Dai, Xiaohu
Abstract: Hydrolysis plays an imperative role in the abiotic transformation process of antibiotics in aqueous solutions. However, little information is available on the hydrolysis process of spectinomycin (an aminocyclitol antibiotic). This study systematically investigated the spectinomycin hydrolysis kinetics and mechanisms under different pH via experiments and density functional theory (DFT) computation. Hydrolysis was first conducted in a pure water system under pH of 4.0–9.0 and temperature of 25 °C, 50 °C and 70 °C, respectively. Results showed that hydrolysis was highly dependent on pH and temperature. When pH > 6.0, spectinomycin hydrolysis was accelerated by the catalysis of OH − . Meanwhile, the hydrolysis rate increased with the elevation of temperature. Then, for the reference of the practical environment, the general base-catalyzed hydrolysis and mechanisms were studied under environmental pH 6.0–8.0 and 25 °C. DFT calculation demonstrated that base-catalyzed hydrolysis of spectinomycin could be more thermodynamically and kinetically favorable based on the lower Gibbs free energies of reaction and Gibbs free energies of activation. Further, instead of specific base catalysis (OH − ), the general base catalysis (e.g., phosphate buffer) was also found to promote hydrolysis efficiency. The antibacterial activity and ecotoxicities of the hydrolysis product were analyzed to be lower than the precursor, thereby decreasing the environmental impact of spectinomycin. Graphical abstract: Image 1 Highlights: Base-catalyzed reaction contributed significantly to hydrolysis at pH > 6.0. Reaction with OH − was more quickly for spectinomycin as its ΔG b was lower. DFT combined with TST could predict the spectinomycin k h under pH 6.0–8.0. Buffer solution could accelerate spectinomycin hydrolysis process. The effects of hydrolysis product on environment were lower than spectinomycin.